Novel Heterozygous Missense Variant in GRIA4 Gene Associated With Neurodevelopmental Disorder With or Without Seizures and Gait Abnormalities - Wang, Hua; Liu, Jiatong; Li, Fuwei; Teng, Ziteng; Liu, Mingyu; Gu, Weiyue (Frontiers in Genetics, 2022)
Objective: Neurodevelopmental disorder with or without seizure and gait abnormalities (NEDSGA, MIM * 617864) is a newly described autosomal dominant inherited disease caused by a heterozygous variant in the GRIA4 gene. GRIA4 plays an essential role in excitatory synaptic transmission. In this study, we presented the clinical and genetic features of a female patient carrying a novel de novo variant in GRIA4, and further reviewed previously reported five different patients. Methods: A detailed history and clinical examination were conducted on the patient. Trio-whole exome sequencing (WES) was performed to identify pathogenic variants in NEDSGA. Sanger sequencing was further used to validate the variants. Results: We described the clinical features of an infant diagnosed with NEDSGA caused by a GRIA4 variant, who presented with severe developmental delay, limb hypertonia, generalized seizure, retinal hypoplasia, and chorioretinal hyperpigmentation. The patient developed tricuspid regurgitation and imaging examination revealed a patent foramen ovale. Trio-WES identified a novel de novo heterozygous missense variant c.1918G>T, p.Ala640Ser in the GRIA4 gene. Multiple in silico tools predicted deleterious effects of p.Ala640Ser. Conclusions: A novel heterozygous missense variant in the GRIA4 gene (c.1918G>T) identified in the proband expanded the genotypic and phenotypic spectrum of disorders associated with GRIA4 variants. This is the first NEDSGA case reported in China. Our findings provide valuable information for the differential diagnosis of neonatal onset neurodevelopmental disorders.